Shared care planning on underage patients (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Shared care planning when the patient is already incapacitated is a decision-making paradigm that allows for the gradual development of awareness among those involved in the decision-making process, as well as the appropriate involvement of multiple professionals. When determining the content of decisions concerning a minor, it is essential to prioritize their best interest and consider the limitations of available medical interventions, assessing both objective and subjective aspects (the effectiveness of the intervention and its tolerability for the patient).
Keywords: Advance care planning; shared care planning; pediatric patient; parents; physician; best interest of the child